Neonatal and Pediatric Organ Donation: Ethical Perspectives and Implications for Policy - Sarnaik, Ajit A. (Frontiers in Pediatrics, 2015)
The lifesaving processes of organ donation and transplantation in neonatology and pediatrics carry important ethical considerations. The medical community must balance the principles of autonomy, nonmaleficence, beneficence, and justice to ensure the best interest of the potential donor and to provide equitable benefit to society. Accordingly, the US Organ Procurement and Transplantation Network (OPTN) has established procedures for the ethical allocation of organs depending on several donor-specific and recipient-specific factors. To maximize the availability of transplantable organs and opportunities for dying patients and families to donate, the US government has mandated that hospitals refer potential donors in a timely manner. Expedient investigation and diagnosis of brain death where applicable are also crucial, especially in neonates. Empowering trained individuals from organ procurement organizations to discuss organ donation with families has also increased rates of consent. Other efforts to increase organ supply include recovery from donors who die by circulatory criteria (DCDD) in addition to donation after brain death (DBD), and from neonates born with immediately lethal conditions such as anencephaly. Ethical considerations in DCDD compared to DBD include a potential conflict of interest between the dying patient and others who may benefit from the organs, and the precision of the declaration of death of the donor. Most clinicians and ethicists believe in the appropriateness of the Dead Donor Rule, which states that vital organs should only be recovered from people who have died. The medical community can maximize the interests of organ donors and recipients by observing the Dead Donor Rule and acknowledging the ethical considerations in organ donation.